Peranan Pejabat daerah Padang Terap Dalam Tindakan Awal/Kesiapsiagaan Menghadapi Banjir (Satu Kajian Kes Padang Terap) - Rita Asmalia, Lubis (2012)
Flooding is the biggest problem that almost every year occur in almost all regions in Malaysia, including Padang Terap District, Kedah. This study aims are to identify how the role/coordination system of Padang Terap District Office in preparation for floods and to identify any action that has been provided by Padang Terap District Office and other agency in Padang Terap District in the face of the possibility of flooding in 2012's. This study focused on early action/preparedness for the possibility of flooding in Year 2012. This study used the Descriptive Qualitative Method, while the result of study observations made during a following the flood meetings and interviews conducted from a few of respondents. This study uses primary data and secondary data. Results of meetings and interviews from a few of respondents is as primary sources when important documents of the organization, projects documentation, as well as literature-literature library as a secondary source. From this study the result that the role of the Padang Terap District Office in face flood problems are as Coordinator (all aid or action that has been prepared by other agencies should be confirmed or submitted in advance to the Padang Terap District Office), as a Catalyst/ Connector (The Padang Terap District Office then the will manage all of the aid and actions that has been prepared), and as a Distributor (Then The Padang Terap District Office will disburse aid or actions that have been prepared to all the flood victims). To deal with the possibility of flooding, Padang Terap District Office cooperate with other agencies in Padang Terap District has provided a number of actions such as providing evacuation centers, food supplies, food base, providing clean water and a toilet at the time of the flood, boat, volunteers and etc. that are needed by the victims. Some suggestions are also available from this study, so hopefully can overcome or avoid flooding in the country of Malaysia, particularly in the Padang Terap District, Kedah Darul Aman.